Chemical Synthesis and Integration of Highly Conductive PdTe2 with Low‐Dimensional Semiconductors for p‐Type Transistors with Low Contact Barriers. Issue 27 (31st May 2021) - Zheng, Jingying; Miao, Tingting; Xu, Rui; Ping, Xiaofan; Wu, Yueyang; Lu, Zhixing; Zhang, Ziming; Hu, Dake; Liu, Lina; Zhang, Qi; Li, Dawei; Cheng, Zhihai; et al.
Abstract: Low‐dimensional semiconductors provide promising ultrathin channels for constructing more‐than‐Moore devices. However, the prominent contact barriers at the semiconductor–metal electrodes interfaces greatly limit the performance of the obtained devices. Here, a chemical approach is developed for the construction of p‐type field‐effect transistors (FETs) with low contact barriers by achieving the simultaneous synthesis and integration of 2D PdTe2 with various low‐dimensional semiconductors. The 2D PdTe2 synthesized through a quasi‐liquid process exhibits high electrical conductivity (≈4.3 × 10 6 S m −1 ) and thermal conductivity (≈130 W m −1 K −1 ), superior to other transition metal dichalcogenides (TMDCs) and even higher than some metals. In addition, PdTe2 electrodes with desired geometry can be synthesized directly on 2D MoTe2 and other semiconductors to form high‐performance p‐type FETs without any further treatment. The chemically derived atomically ordered PdTe2 –MoTe2 interface results in significantly reduced contact barrier (65 vs 240 meV) and thus increases the performance of the obtained devices. This work demonstrates the great potential of 2D PdTe2 as contact materials and also opens up a new avenue for the future device fabrication through the chemical construction and integration of 2D components. Abstract : The patterned synthesis of high‐quality 2D PdTe2 is demonstrated. The as‐grown PdTe2 exhibits high electrical and thermal conductivities, showing potential as an ideal contact material in nanoelectronics. Based on the nondestructive synthesis of PdTe2 patterns directly on various low‐dimensional semiconductors, high‐performance field‐effect transistors (FETs) with reduced contact barriers are chemically constructed.